Probing the Molecular Mechanisms in Copper Amine Oxidases by Generating Heterodimers. Issue 4 (21st January 2015) - Gaule, Thembaninkosi G.; Smith, Mark A.; Pearson, Arwen R.; Knowles, Peter F.; McPherson, Michael J.
Abstract For some homodimeric copper amine oxidases (CuAO), there is suggestive evidence of differential activity at the two active sites implying potential cooperativity between the two monomers. To examine this phenomenon for the Arthrobacter globiformis CuAO (AGAO), we purified a heterodimeric form of the enzyme for comparison with the homodimer. The heterodimer comprises an active wild‐type monomer and an inactive monomer in which an active‐site tyrosine is mutated to phenylalanine (Y382F). This mutation prevents the formation of the trihydroxyphenylalanine quinone (TPQ) cofactor. A pETDuet vector and a dual fusion tag strategy was used to purify heterodimers (WT/Y382F) from homodimers. Purity was confirmed by western blot and native PAGE analyses. Spectral and kinetic studies support the view that whether there are one or two functional monomers in the dimer, the properties of each functional monomer are the same, thus indicating no communication between the active sites in this bacterial enzyme.